Impact of Land Use Changes Due to Tourism on Ecosystem Services Using InVEST: Case Study: Badung Regency, Bali - Alfandi, Atanasius; Transver Wijaya, Yuliagnis (Politeknik Statistika STIS, 2025)
Ecosystem services play a vital role in supporting human life and environmental sustainability. However, tourism activities in Badung Regency, Bali, have led to significant changes in land cover and use, impacting the function of ecosystem services. This study integrates remote sensing, machine learning, and InVEST technology to understand the impact of Land Use/Land Cover (LULC) changes on ecosystem services in Badung Regency. The results show a decrease in non agricultural vegetation area from 17659.65 hectares in 2014 to 11405.84 hectares in 2024. Meanwhile, built-up land experienced a drastic increase from 15074.47 hectares in 2014 to 22134.06 hectares in 2024. In addition, the InVEST model shows a decrease in carbon stock by 1379,841.68 tons in the period 2014 to 2024. Meanwhile, water yield, nitrogen export, and sediment export increased, reflecting a relationship between tourism development and the decline in ecosystem services. Correlation analysis shows a consistent negative correlation between water yield and carbon stock, as well as a positive correlation between nitrogen export and sediment export. The results of this study are expected to serve as a reference for further studies on the dynamics of ecosystem services and support sustainable environmental management efforts in areas with rapidly growing tourism activity.